PENERAPANA METODE NATIONAL INSTITUTE OF STANDARS AND TECHNOLOGY (NIST) DALAM ANALISIS FORENSIK DIGITAL UNTUK PENANGANAN CYBER CRIME - Mulia Fitriana; Khairan AR AR; Jiwa Malem Marsya (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
The development of technology is currently developing very quickly, this is directly proportional to releasing cyber crime. One crime that often occurs is the case of Pornography. This application is done using one of the very popular Instant Messenger (IM) applications, the WhatsApp application. But after the crime is committed next or sending evidence in the form of conversations, video recordings, images and others committed by the suspect using the WhatsApp application. Therefore, this study proposes to find evidence related to digital pornography. This research produced a forensic procedure in conducting an investigation of the WhatsApp application to obtain previously published evidence containing a conversation session, a list of contact numbers, a profile photo of the victim and others. This research was conducted by reading a backup file of the encrypted WhatsApp application database that stores the conversation session that has been released. This research uses the method (National Institute of Standards and Technology (NIST). This digital evidence can be obtained using one of the forensic tools namely WhtasApp Viewer. The results obtained in this study contain WhatsApp contents that have been available which can be found digitally in uncovering the crime of pornography that is happen.